Dissemination of technology information through YouTube: a case of renewable energy technology - Muhammad Kunta Biddinika; Mochamad Syamsiro; Srikandi Novianti; Bakhtiyor Nakhshiniev; Muhammad Aziz; Fumitake Takahashi (Universitas Ahmad Dahlan, 2019)
Internet video sharing has been used by scholars for two main purposes. First, it is for informal scholarly communication including teaching and academic conferences. Second, it is for engagement tool by contemporary society. Renewable energy technology has also been utilizing internet video sharing technology for those purposes. It is a promotional tool to disseminate information about the technology as well as a media for public engagement with renewable energy issues. This paper reviews how YouTube, the most popular internet video sharing website whose content is created and accessed publicly for free of charge, has been elaborated in scholarly publication in the various fields prior to showing how renewable energy is portrayed in YouTube. By using a hundred YouTube most viewed videos, this paper presents an in-depth and systematic measurement study on the characteristics of YouTube videos on renewable energy issues.